Solvent-Free Synthesis of α-Amino Ketones from α-Hydroxyl Ketones via A Novel Tandem Reaction Sequence Based on Heyns Rearrangement - Li, Ling-yu; Zeng, Qing-le; Li, Guang-xun; Tang, Zhuo (Synlett, 2019)
Heyns rearrangement have been famous for carbohydrate chemists for several decades. However, this reaction was underrated as a useful method for synthetic chemists due to preparative shortcomings. Herein we developed an efficient method for the synthesis of pharmaceutically important α-amino ketones from readily available α-hydroxy ketones and secondary amines through a tandem reaction sequence based on Heyns rearrangement. The reaction smoothly proceeded by using catalytic PTSA as catalyst without solvent. Primary and secondary α-hydroxy ketones were readily used and regioselectively afforded the correspondingly α-amino ketones with moderate yield.
Keywords: Heyns rearrangement; α-amino ketone; solvent-free; α-hydroxyl ketone; tandem reaction